RAPID VERIFICATION OF VIRUS PARTICLE PRODUCTION FOR A PERSONALIZED VACCINE (2019)
Methods for rapidly confirming production of infectious viral vectors, for use in clinical grade personalized neo-antigen vaccines for subjects in need thereof, are provided.